Role of GTPase-Dependent Mitochondrial Dynamins in Heart Diseases - Jiangen Liu; Xianjing Song; Youyou Yan; Bin Liu (Frontiers in Cardiovascular Medicine, 2021)
Heart function maintenance requires a large amount of energy, which is supplied by the mitochondria. In addition to providing energy to cardiomyocytes, mitochondria also play an important role in maintaining cell function and homeostasis. Although adult cardiomyocyte mitochondria appear as independent, low-static organelles, morphological changes have been observed in cardiomyocyte mitochondria under stress or pathological conditions. Indeed, cardiac mitochondrial fission and fusion are involved in the occurrence and development of heart diseases. As mitochondrial fission and fusion are primarily regulated by mitochondrial dynamins in a GTPase-dependent manner, GTPase-dependent mitochondrial fusion (MFN1, MFN2, and OPA1) and fission (DRP1) proteins, which are abundant in the adult heart, can also be regulated in heart diseases. In fact, these dynamic proteins have been shown to play important roles in specific diseases, including ischemia-reperfusion injury, heart failure, and metabolic cardiomyopathy. This article reviews the role of GTPase-dependent mitochondrial fusion and fission protein-mediated mitochondrial dynamics in the occurrence and development of heart diseases.